2018
DOI: 10.1016/j.celrep.2018.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Splice-Site-Creating Mutations in Cancer

Abstract: SUMMARYFor the past decade, cancer genomic studies have focused on mutations leading to splice-site disruption, overlooking those having splice-creating potential. Here, we applied a bioinformatic tool, MiSplice, for the large-scale discovery of splice-site-creating mutations (SCMs) across 8,656 TCGA tumors. We report 1,964 originally mis-annotated mutations having clear evidence of creating alternative splice junctions. TP53 and GATA3 have 26 and 18 SCMs, respectively, and ATRX has 5 from lower-grade gliomas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
191
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(196 citation statements)
references
References 54 publications
3
191
2
Order By: Relevance
“…Our results contrast with another TCGA study that investigated alternative mRNA splicing 21 and demonstrated a limited set of non-constitutive exon-exon junctions attributable to cis-acting splicing mutations (n = 32). The 2,736 novel or rare variants that we report which specifically activate cryptic splicing (significant 'junction-spanning cryptic site use' reads found by Veridical), exceed the number reported in another study that analyzed all available TCGA tumor transcriptomes (n=1,964) 22 .…”
Section: Resultscontrasting
confidence: 67%
“…Our results contrast with another TCGA study that investigated alternative mRNA splicing 21 and demonstrated a limited set of non-constitutive exon-exon junctions attributable to cis-acting splicing mutations (n = 32). The 2,736 novel or rare variants that we report which specifically activate cryptic splicing (significant 'junction-spanning cryptic site use' reads found by Veridical), exceed the number reported in another study that analyzed all available TCGA tumor transcriptomes (n=1,964) 22 .…”
Section: Resultscontrasting
confidence: 67%
“…Few tools are directed at linking aberrant splicing to variants in cis, and most are tailored to the authors' particular aims (Jayasinghe et al , 2018 ;Pertea et al , 2001 ;Jung et al , 2015) . RegTools is designed for broad applicability and computational efficiency ( Supplementary Figure 14) .…”
Section: Application To Tumor Samplesmentioning
confidence: 99%
“…RNA sequencing data for 9,583 tumors from 32 cancer types were downloaded from the cgHub repository on December 18, 2015, and aligned to the hg19 human genome assembly, 14 excluding alternative haplotype regions, with hisat 62 0.1.6-beta (parameters: "--no-mixed -no-discordant --no-unal --known-splicesite-infile"), using splice junctions defined in the GENCODE (version 19) reference human genome annotation. Gene read counts were derived with htseq-count 54 (parameters: "-m intersection-strict -s no").…”
Section: Transcriptome Comparison With Tumors From Tcgamentioning
confidence: 99%